3(v-6)-2=-2(-9v+7)-v

Simple and best practice solution for 3(v-6)-2=-2(-9v+7)-v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(v-6)-2=-2(-9v+7)-v equation:



3(v-6)-2=-2(-9v+7)-v
We move all terms to the left:
3(v-6)-2-(-2(-9v+7)-v)=0
We multiply parentheses
3v-(-2(-9v+7)-v)-18-2=0
We calculate terms in parentheses: -(-2(-9v+7)-v), so:
-2(-9v+7)-v
We add all the numbers together, and all the variables
-1v-2(-9v+7)
We multiply parentheses
-1v+18v-14
We add all the numbers together, and all the variables
17v-14
Back to the equation:
-(17v-14)
We add all the numbers together, and all the variables
3v-(17v-14)-20=0
We get rid of parentheses
3v-17v+14-20=0
We add all the numbers together, and all the variables
-14v-6=0
We move all terms containing v to the left, all other terms to the right
-14v=6
v=6/-14
v=-3/7

See similar equations:

| 6-3r-1=-13 | | 4v-3v=10 | | F(3)=g(4) | | (6x+5=4x+45 | | 30+1.50x=40 | | 5(-5a+5)+4(5-a)=-13 | | 8×2(-1+m)+3×2=2×2(m-2) | | 5x+2-2(x-1)=3x-4 | | 8x-5(x+9)=4x-5 | | Z=4/9t+4;t | | (x^2)=16 | | 5x2-25=100 | | .10d=4.95 | | x=4=20 | | -3x-47=-17 | | 24+12n=15n | | 0.75/2=3/m | | 4(x-3)=2x-9+1 | | (x-20)/4=5 | | 6x-2-8x=-12 | | 3.9+0.79x=1.09x | | (x^2)=2x | | 11=2x+10 | | 5x+31=11 | | 4.2=v/2.6 | | 5x-14=7x+26 | | 9(7x-3)=603 | | 13w-12w=5 | | 7x14-3x=30 | | 7x+2=2(2x+5) | | -7(x-2)+5(3-x)-4x=-12x+13 | | 8w+4-2(-5w-2)=4(w-1) |

Equations solver categories